Hydrophobic and Basic Domains Target Proteins to Lipid Droplets - Ingelmo-Torres, Mercedes (2009)
In recent years, progress in the study of the lateral organization of the plasma membrane has led to the proposal that mammalian cells use two different organelles to store lipids: intracellular lipid droplets (LDs) and plasma membrane caveolae. Experimental evidence suggests that caveolin (CAV) may act as a sensitive lipid-organizing molecule that physically connects these two lipid-storing organelles. Here, we determine the sequences necessary for efficient sorting of CAV to LDs. We show that targeting is a process cooperatively mediated by two motifs. CAV's central hydrophobic domain (Hyd) anchors CAV to the endoplasmic reticulum (ER). Next, positively charged sequences (Pos-Seqs) mediate sorting of CAVs into LDs. Our findings were confirmed by identifying an equivalent, non-conserved but functionally interchangeable Pos-Seq in ALDI, a bona fide LD-resident protein. Using this information, we were able to retarget a cytosolic protein and convert it to an LD-resident protein. Further studies suggest three requirements for targeting via this mechanism: the positive charge of the Pos-Seq, physical proximity between Pos-Seq and Hyd and a precise spatial orientation between both motifs. The study uncovers remarkable similarities with the signals that target proteins to the membrane of mitochondria and peroxisomes